COMMUNITY SERVICE EDUCATION RELATED TO ABDOMINAL MASSAGE FOR PREGNANT WOMEN IN KARO TRIBAL CULTURE IN MEDAN TUNTUNGAN DISTRICT - Barirah; Fistaqul Isnaini; Nelly Rahayu (Cattleya Darmaya Fortuna, 2024)
The practice of abdominal massage for pregnant women is one of the cultural traditions that is still inherent in the community, including in the culture of the Karo Tribe in Medan Tuntungan District. Although considered a traditional form of care, this practice is often not based on proper medical understanding, so it has the potential to pose a risk to the health of the mother and fetus if done unsafely. This community service activity aims to provide education about the safety of abdominal massage practices in the Karo Tribal culture, as well as increase pregnant women's understanding of the medical risks that may arise. The program was held on May 21, 2024 with interactive counseling methods and in-depth discussions to align cultural practices with pregnancy-safe health principles. The results of the evaluation showed that there was an increase in participants' knowledge in recognizing the limitations of safe massage practice, so that it is expected to be able to prevent the risk of pregnancy complications due to improper actions.